Strategic Communication Networks - HAGENBACH, JEANNE; KOESSLER, FRÉDÉRIC (Review of Economic Studies, 2009)
We consider situations in which every agent would like to take an action that is coordinated with those of others, as well as close to a common state of nature, with the ideal proximity to that state varying across agents. Before this coordination game is played, agents decide to whom they reveal their private information about the state. The information transmission occurring in the cheap-talk communication stage is characterized by a strategic communication network whose links represent truthful information transmission. In equilibrium, whether communication takes place between two agents depends not only on the conflict of interest between these agents, but also on the number and preferences of the other agents with whom they communicate. In particular, communication to a large group of recipients may be feasible even though communication to a small subset of that group may not be. We show that agents who are more central in terms of preference tend to communicate more and to have a greater impact on decisions.